ATF4-induced warburg metabolism drives over-proliferation in drosophila - Sorge, Sebastian; Theelke, Jonas; Yildirim, Kerem; Lohmann, Ingrid (Cell reports, 2020)
The mitochondrial electron transport chain (ETC) enables essential metabolic reactions; nonetheless, the cellular responses to defects in mitochondria and the modulation of signaling pathway outputs are not understood. We show that Notch signaling and ETC attenuation via knockdown of COX7a induces massive over-proliferation. The tumor-like growth is caused by a transcriptional response through the eIF2α-kinase PERK and ATF4, which activates the expression of metabolic enzymes, nutrient transporters, and mitochondrial chaperones. We find this stress adaptation to be beneficial for progenitor cell fitness, as it renders cells sensitive to proliferation induced by the Notch signaling pathway. Intriguingly, over-proliferation is not caused by transcriptional cooperation of Notch and ATF4, but it is mediated in part by pH changes resulting from the Warburg metabolism induced by ETC attenuation. Our results suggest that ETC function is monitored by the PERK-ATF4 pathway, which can be hijacked by growth-promoting signaling pathways, leading to oncogenic pathway activity.